Perbandingan Peraturan Penanaman Modal Asing dan Penanaman Modal dalam Negeri di Indonesia (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
This study examines the legal implications of the regulation of foreign investment (FDI) and domestic investment within the Indonesian legal system, as well as its relation to national economic sovereignty. The background of this research is rooted in the need of developing countries, including Indonesia, to attract investment in order to promote economic growth while still safeguarding national interests as mandated by the constitution. This research employs a normative juridical method with statutory and conceptual approaches. The results show that although foreign and domestic investments are regulated under a single legal framework through Law Number 25 of 2007, there are significant differences in terms of legal subjects, business entities, as well as ownership and sectoral restrictions. These differences do not constitute discrimination, but rather reflect the state’s protective legal policy. On the other hand, foreign investment brings positive impacts such as capital inflow, technology transfer, and market expansion. However, it also poses potential risks, including economic dependency and reduced policy autonomy. Therefore, a balance between investment openness and regulatory control is necessary to ensure that economic sovereignty is maintained and the benefits of investment can be optimally realized for society.